Integrating Hybrid Learning, YouTube Tutorials, and AI Tools to Enhance Student Engagement and Achievement in Introductory Physics: A Mixed-Methods Study in Mathematics Education - Muhammad Taufik; Syahrial A (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study investigates the effectiveness of integrating hybrid learning, YouTube tutorials, and artificial intelligence (AI) tools in improving student engagement and academic performance in an introductory physics course for second-semester mathematics education students. A mixed-methods design was employed, combining quantitative data from pre- and post-tests, usage logs of YouTube and AI platforms, and class participation records, along with qualitative insights from student feedback. Descriptive statistics and inferential analyses reveal a significant improvement in post-test scores, with an average increase of 9 points (from 70.2 to 79.4), indicating the positive impact of the digital learning interventions. Students’ engagement, particularly measured through their interaction with AI-based personalized feedback and video tutorials, correlated strongly with learning outcomes. The findings suggest that leveraging hybrid learning environment supported by visual and adaptive tools can foster deeper understanding of abstract physics concepts and promote active participation.